2018
DOI: 10.1002/tea.21446
|View full text |Cite
|
Sign up to set email alerts
|

Students' mental load, stress, and performance when working with symbolic or symbolic–textual molecular representations

Abstract: In science education, representations are necessary inter alia for the understanding of relationships between structures and systems. However, several studies have identified difficulties of students when working with representations. In the present study, we investigated students' responses (regarding their preference, test performance, mental load (ML), and stress) toward two kinds of representations: symbolic representations, which only use abstract symbols, versus combined symbolic–textual representations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…Thus, it is plausible to assume a relationship between subjective measures and heart rate-or hormone-based objective measures of cognitive load, which is rarely investigated yet. One study of the authors found a significant positive correlation between selfreported mental load (i.e., perceived task complexity) and perceived stress but no or rather small correlations between self-reported mental load and physiological stress responses (cortisol concentration, heart rate variability; Minkley et al, 2018). Veltman and Gaillard (1993) report similar findings and conclude that cortisol concentration might not be a valid indicator for mental activity and that heart rate variability might indicate cognitive load only in high demanding tasks.…”
Section: Objective Measures Of Cognitive Loadmentioning
confidence: 98%
See 4 more Smart Citations
“…Thus, it is plausible to assume a relationship between subjective measures and heart rate-or hormone-based objective measures of cognitive load, which is rarely investigated yet. One study of the authors found a significant positive correlation between selfreported mental load (i.e., perceived task complexity) and perceived stress but no or rather small correlations between self-reported mental load and physiological stress responses (cortisol concentration, heart rate variability; Minkley et al, 2018). Veltman and Gaillard (1993) report similar findings and conclude that cortisol concentration might not be a valid indicator for mental activity and that heart rate variability might indicate cognitive load only in high demanding tasks.…”
Section: Objective Measures Of Cognitive Loadmentioning
confidence: 98%
“…Besides the measurement of the heart rate itself (heart rate, e.g., Solhjoo et al, 2019), some heart rate variability measures were also used in educational and psychological research, including the ratio between high frequency and low frequency components (LF/HF ratio, e.g., Minkley et al, 2018), and the time-related root mean square of successive differences (RMSSD, e.g., Minkley et al, 2018). If a person is confronted with a complex problem or task, where demands exceed their resources, the RMSSD typically decreases (e.g., Malik et al, 1996), as it represents parasympathetic activity which in turn characterizes relaxation (Laborde et al, 2017).…”
Section: Objective Measures Of Cognitive Loadmentioning
confidence: 99%
See 3 more Smart Citations